2011
DOI: 10.5505/tjtes.2011.70493
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of procalcitonin and phosphorus in acute mesenteric ischemia

Abstract: AMAÇAkut mezenter iskemi (AMİ) modeli kullanılarak yapılan bu çalışmada, serum prokalsitonin ve fosfor düzeylerinin AMİ erken tanısında kullanılabilirliği araştırıldı. GEREÇ VE YÖNTEMÇalışmada 21 adet Yeni Zelanda tavşanı kullanıldı. Denekler Kontrol, Sham ve İskemi grubu olarak adlandırıl-dı. Kontrol grubundaki deneklere herhangi bir girişim yapılmadı. Sham ve İskemi grubundaki deneklere orta hat insizyonu ile laparotomi yapıldı. İskemi grubundaki deneklere ise laparatomi yapıldıktan sonra süperior mezenterik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 16 publications
1
20
0
2
Order By: Relevance
“…[1] It is not very common, but demonstrates significantly high mortality, and requires immediate diagnosis and therapeutic intervention. [11] Early diagnosis is difficult; however, delayed diagnosis increases mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1] It is not very common, but demonstrates significantly high mortality, and requires immediate diagnosis and therapeutic intervention. [11] Early diagnosis is difficult; however, delayed diagnosis increases mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Treatment options include methods ranging from radiological intervention to surgical methods. [21] Early diagnosis and appropriate treatment intervention reduce mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Steinwald et al (20) reported that PCT levels can be used as a marker for the degree of sepsis and mortality. In a study investigating whether PCT levels can be used in the early diagnosis of AMI in an experimental AMI model, Karabulut et al (21) reported that PCT levels rise in the early period in AMI and can be used as a diagnostic and prognostic marker.…”
Section: Discussionmentioning
confidence: 99%